2022
DOI: 10.1007/s12094-022-02985-7
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection in patients with melanoma: results of the Spanish Melanoma Group registry

Abstract: Background The Spanish Melanoma Group (GEM) developed a national registry of patients with melanoma infected by SARS-CoV-2 (“GRAVID”). Methods The main objective was to describe the COVID-19 fatality rate in patients with melanoma throughout the pandemic, as well as to explore the effect of melanoma treatment and tumor stage on the risk of COVID-19 complications. These are the final data of the register, including cases from February 2020 to September 2021. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Retrospective cohort studies comprised the majority of the included studies, with five (citations 44, 45, 47, 49, 53) being prospectively designed. Among the 15 studies included, four ( 39 , 41 , 42 , 46 ) were performed in the United States, five ( 40 , 44 , 47 , 50 , 52 ) in Italy, four ( 45 , 48 , 49 , 53 ) in Spain, one ( 51 ) in China, and one ( 43 ) in France. All patients in the 15 studies had solid tumors: three of the studies ( 41 , 48 , 51 ) involved patients with lung cancer, one study ( 46 ) included patients with gynecological tumors, and another study ( 45 ) included patients with melanoma; the remaining 10 studies were not specific as to cancer type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective cohort studies comprised the majority of the included studies, with five (citations 44, 45, 47, 49, 53) being prospectively designed. Among the 15 studies included, four ( 39 , 41 , 42 , 46 ) were performed in the United States, five ( 40 , 44 , 47 , 50 , 52 ) in Italy, four ( 45 , 48 , 49 , 53 ) in Spain, one ( 51 ) in China, and one ( 43 ) in France. All patients in the 15 studies had solid tumors: three of the studies ( 41 , 48 , 51 ) involved patients with lung cancer, one study ( 46 ) included patients with gynecological tumors, and another study ( 45 ) included patients with melanoma; the remaining 10 studies were not specific as to cancer type.…”
Section: Resultsmentioning
confidence: 99%
“…Retrospective cohort studies comprised the majority of the included studies, with five (citations 44, 45, 47, 49, 53) being prospectively designed. Among the 15 studies included, four (39,41,42,46) were performed in the United States, five (40, 44, 47, 50, 52) in Italy, four (45,48,49,53) in Spain, one (51) in China, and one (43)…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nevertheless, our results are in line with those of previous studies in melanoma patients. The GRAVID study by the Spanish Melanoma Group reported that stage and melanoma treatment did not affect prognosis in a cohort of 150 unvaccinated melanoma patients [ 25 ]. Similarly, Johnson et al reported that melanoma therapy, irrespective of modality, was not associated with severity of COVID-19 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both molecularly targeted treatments (for BRAF mutated cases) and immunotherapy with immune checkpoint inhibitors (ICIs) are first-line treatment options for advanced disease [ 22 ]. Evidence on the impact of melanoma and its treatment on COVID-19 severity and survival are scarce and derive mostly from early studies that include small numbers of patients [ 19 , 23 ] and melanoma registry-based studies [ 24 , 25 , 26 ]. The present study is an analysis of 121 melanoma patients treated at a large academic tertiary referral center in Greece who were diagnosed with COVID-19.…”
Section: Introductionmentioning
confidence: 99%